The Transition From Maternity Blues to Full-Blown Perinatal Depression: Results From a Longitudinal Study - Luciano, Mario; Sampogna, Gaia; Del Vecchio, Valeria; Giallonardo, Vincenzo; Perris, Francesco; Carfagno, Marco; Raia, Maria Luce; Di Vincenzo, Matteo; La Verde, Marco; Torella, Marco; Fiorillo, Andrea (Frontiers in Psychiatry, 2021)
Background: Aims of the present study are to: 1) assess the frequency of maternity blues (MB); 2) identify the clinical and social characteristics more frequently associated with the onset of depressive symptoms after delivery; and 3) verify the hypothesis that the presence of maternity blues is a risk factor for the onset of a depressive episode in the 12 months after delivery. Methods: This is a longitudinal observational study. All pregnant women who gave birth at the inpatient unit of Gynaecology and Obstetrics of the University of Campania “Luigi Vanvitelli” from December 2019 to February 2021 have been invited to participate in the study. Upon acceptance, women were asked to complete the Italian version of the Edinburgh Postnatal Depression Scale along with an ad-hoc questionnaire on the women’s sociodemographic, gynaecological and peripartum characteristics as well as their psychiatric history. Women have been reassessed after one, three, six and eleven months. Results: A total of 359 women were recruited within three days from delivery, with a mean EPDS total score of 5.51 (±4.20). Eighty-three women (23.1%) reported the presence of maternity blues. Mean EPDS total scores were 12.8 (±0.2) in the MB group vs. 4.26 (±0.2) in the group without MB (p<.0001). MB predictors were the presence of an anxiety disorder with an onset six months prior to pregnancy, of preeclampsia, of increased foetal health rate, of conflicts with relatives other than partner and having a partner with an anxiety disorder. At multivariate analyses the presence of MB increased 7-time the risk to have a higher EPDS score at follow-up assessments (OR: 7.79; CI: 6.88-8.70, p<.000). This risk is almost four times higher one months after the delivery (OR: 4.66; CI: 2.54 – 6.75, p<.000), almost three times higher after three months (OR: 2.98; CI: 0.50 – 5.46, p<.01) and almost six times higher after twelve months (OR: 5.88; CI: 3.20 – 8.54, p<.000). Conclusions: Although MB was a self-limiting condition in the majority of cases, depressive symptoms arose quite often immediately after the childbirth. Professionals should be trained to monitor symptoms of MB and its transition toward a depressive episode